2018
DOI: 10.9775/kvfd.2018.20055
|View full text |Cite
|
Sign up to set email alerts
|

Akkaraman Kuzularında DGAT1, CAST ve IGF-I Gen Polimorfizmleri ve Sütten Kesim Yaşına Kadarki Canlı Ağırlık Artışı Üzerine Etkileri

Abstract: Early live weight in sheep is important for lamb survival and average weight gain until slaughter. The aim of the present study was to investigate association between CAST-MspI, DGAT1-AluI and IGF-1-Bsp143II polymorphisms and early live weights between birth and weaning age in Akkaraman lambs. A total of 374 lambs were genotyped for CAST-MspI, DGAT1-AluI and IGF-1-Bsp143II polymorphisms by the polymerase chain reaction and restriction length polymorphism (PCR-RFLP) method. The results of PCR-RFLP analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…All of the examined animals were found to be BB genotype carriers. Similarly, Bayram et al (2019) have reported that lambs of the Akkaraman breed were found to have the monomorphic BB genotype. On the contrary, He et al (2012) showed that all three genotypes (AA, AB, and BB) were present in Small Tail Han sheep and Hu sheep breeds.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…All of the examined animals were found to be BB genotype carriers. Similarly, Bayram et al (2019) have reported that lambs of the Akkaraman breed were found to have the monomorphic BB genotype. On the contrary, He et al (2012) showed that all three genotypes (AA, AB, and BB) were present in Small Tail Han sheep and Hu sheep breeds.…”
Section: Discussionmentioning
confidence: 86%
“…However, the MN genotype frequency was quite lower in both sheep breeds they studied (Khan et al, 2012). Indeed, several studies have indicated that the MM genotype is predominant in various sheep breeds worldwide (Bayram et al, 2019;Dincel et al, 2015;Gabor et al, 2009;Gorlov et al, 2016;Khan et al, 2012). Gabor et al (2009) have reported that the MM has the highest genotype frequency in Tsigai sheep and Tsigai × Lacaune crossbreds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the molecular studies on meat yield in Turkish sheep breeds have been performed on the cast, leptin, and a few other genes, while the CLPG gene was studied less (Balcıoğlu et al, 2014;Bayram et al, 2019;Kırıkçı et al, 2021;Kırıkçı, 2022). In addition, there is currently no study that describes the genetic structure of the Akkaraman sheep breed for the CLPG gene.…”
Section: Introductionmentioning
confidence: 99%